2022
DOI: 10.1111/gwao.12832
|View full text |Cite
|
Sign up to set email alerts
|

Heroism and/as injurious speech: Recognition, precarity, and inequality in health and social care work

Abstract: This paper draws on Judith Butler's (2009Butler's ( , 1997 writing on precarity and the interpellatory power of naming, read through her recent writing on the dynamics of recognition, vulnerability, and resistance, to develop a critique of the discourse of heroism used to position health and social care professionals, and other key workers, during the COVID pandemic. It does so in order to reflect on the insights into workplace inequalities that this example provides, in particular into what, to borrow from Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Triggered by the COVID‐19 pandemic, scholars have explicitly discussed vulnerability as an epistemological praxis, that is the role of vulnerability in the research process (Abdellatif & Gatto, 2020; Henriksen et al., 2022; Plester et al., 2022), and how vulnerabilities become visible when infrastructures break down (Clavijo, 2020; Ryan et al., 2021). Hales and Tyler (2022), for example, critique the heroism discourse surrounding healthcare and social workers using a Butlerian lens. Inspired by Butler's work on vulnerability and resistance (Butler, 2016), scholars have recently studied how individuals and groups use vulnerability for resistance (Cutcher et al., 2022; Gao & Sai, 2021; Reiss et al., 2021).…”
Section: Current Discussion On Vulnerability In the Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Triggered by the COVID‐19 pandemic, scholars have explicitly discussed vulnerability as an epistemological praxis, that is the role of vulnerability in the research process (Abdellatif & Gatto, 2020; Henriksen et al., 2022; Plester et al., 2022), and how vulnerabilities become visible when infrastructures break down (Clavijo, 2020; Ryan et al., 2021). Hales and Tyler (2022), for example, critique the heroism discourse surrounding healthcare and social workers using a Butlerian lens. Inspired by Butler's work on vulnerability and resistance (Butler, 2016), scholars have recently studied how individuals and groups use vulnerability for resistance (Cutcher et al., 2022; Gao & Sai, 2021; Reiss et al., 2021).…”
Section: Current Discussion On Vulnerability In the Fieldmentioning
confidence: 99%
“…Resonating the COVID‐19 pandemic, critical and feminist MOS researchers have started to use vulnerability as a praxis of knowing (cf. Abdellatif & Gatto, 2020; Clavijo, 2020; Hales & Tyler, 2022; Henriksen et al., 2022; Plester et al., 2022; Ryan et al., 2021). As invulnerability is an impossibility, Fineman (2010) calls for a government to be a “responsive state”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes vulnerability not simply a curse but possibly also a ground for new modes of solidarity (Butler et al., 2016, p. x). Organization scholars have explored vulnerability as resistance to workplace inequalities (Hales & Tyler, 2022), to patriarchal power structures and gendered dynamics in research processes (Plester et al., 2022), to worsened job and domestic conditions in the context of the COVID‐19 pandemic (Reiss et al., 2021), and to the discrimination against aging subjects in organizational recognition schemes (Cutcher et al., 2022). Thus, these studies have shown that, as an experience of exposure to power, vulnerability can simultaneously constitute an embodied enactment of resistance (Butler, 2016b; Cutcher et al., 2022; Meriläinen et al., 2022).…”
Section: The Self‐making Of the (Future) Female Workermentioning
confidence: 99%